'Acting in the Real World': Acting Methodologies, Power and Gender. Issue 3 (7th March 2019) - WILLIS, EMMA
Abstract : What does the #MeToo movement reveal about how acting is understood at the present time, both in practice and by the public at large? The claim of one convicted abuser, New Zealand acting coach Rene Naufahu, was that his sexual offending in the classroom was simply preparing his students for the 'real world of acting'. Drawing from Elin Diamond's argument that dramatic realism does not simply reflect the real but in fact produces it, I examine how figures like Naufahu promulgate certain notions of acting in order to produce a reality that legitimates abusive behaviour. Furthermore, I suggest that this behaviour is often a performance of acting itself whereby the actor, director or coach, in a selectively self-reflexive manner, exploits their professional 'role' in order to exert power over their victim. I argue that one way of contesting real-world practices that rely on hegemonic assumptions of what acting is or should be is to redeploy the critical terminology of acting to analyse and expose such abuses for the acts that they are.